Medical tourism in developing countries. - Peach, Nate (PASOS Revista de Turismo y Patrimonio Cultural, 2009)
Medical Tourism in Developing Countries is a comprehensive study of the growing synergy between medical services and tourism. The authors successfully present both the economic and legal fundamentals of this rapidly growing industry. Anyone from those wishing to increase their understanding of medical tourism to policy makers seeking specific recommendations on how to develop the sector will benefit from reading this work.